The Effect of Coretax System on Public Financial Performance in Indonesia - Sulkipli Sulkipli; Ramlah Ramlah; Halida Sasmita; Nur Aida; Fitri Indah Sari (LP2M IBK Nitro, 2026)
This study examines the effect of the Core Tax Administration System (Coretax) on public financial performance in Indonesia. As part of Indonesia’s broader fiscal reform agenda, Coretax was introduced to modernize tax administration through system integration, digital automation, and enhanced compliance monitoring. Drawing on fiscal capacity theory and digital transformation frameworks, this research investigates whether the implementation of Coretax contributes to improvements in revenue mobilization, revenue effectiveness, and administrative efficiency. Using a quantitative explanatory design, the study analyzes secondary time-series data on tax revenue, cost of collection ratios, and revenue effectiveness indicators before and after system implementation. Regression analysis and difference-in-means testing are employed to assess the statistical significance of the reform’s impact. The findings indicate that Coretax implementation is positively and significantly associated with higher tax revenue realization, improved revenue effectiveness ratios, and reduced administrative cost ratios. Although minor transitional volatility is observed during the early phase of implementation, the overall results suggest that digital tax administration reform strengthens fiscal capacity and enhances public financial performance. This study contributes to the literature on public sector management and revenue administration reform by providing macro-level empirical evidence from an emerging economy context. The findings offer policy implications for governments seeking to improve fiscal sustainability through digital transformation in tax administration.